La réception des conversations quotidiennes. Communication ordinaire et normativité sociale - Lisandre Labrecque-Lebeau (Communiquer)
The reception of everyday conversation is a question that has not much been explored, neither in communication studies nor in sociology of interaction. This paper presents and conceptualizes what would constitute different moments of that said individual reception, starting from a specific material, that of conversation narratives. Twenty persons from diverse social backgrounds reported all the conversations they had the past seven days in a debriefing with the researcher. These accounts are telling us that the reception process is taking place ahead, in action and presence, and afterwards the conversation is held. Furthermore, we are presenting dimensions of the conversational reception that are speaking of its collective dimension, its immediacy, and its interaction with the internal conversation of interlocutors. This process is taking a constitutive part of ordinary socialization, of everyday intersubjective relations and of social normativity.